2010
DOI: 10.1590/s0104-11692010000400016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Organizational Aspects of a Clinical Emergency Department: A Study in a General Hospital in Ribeirao Preto, SP, Brazil

Abstract: Demand for the Emergency Department (ED) has increased, making the organization of work difficult. This quantitative, descriptive and documental study identifies and analyzes the characteristics of clinical care in the ED of a General Hospital in Ribeirão Preto, SP, in 2007, according to organizational variables. The study population included all clinical care consultations registered in the Hospital Management Information System. Data were analyzed through descriptive statistics and discussed considering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
0
15
0
5
Order By: Relevance
“…In another study conducted in Ribeirão Preto, Coelho et al 20 reported that 39.8% of patients remained for less than six hours and 27.4%, between 24 and 30 hours, with no mention to the type of specialty. Statistical analysis showed that there was an association between length of stay and surgical specialty (Tables 1 and 2).…”
mentioning
confidence: 98%
“…In another study conducted in Ribeirão Preto, Coelho et al 20 reported that 39.8% of patients remained for less than six hours and 27.4%, between 24 and 30 hours, with no mention to the type of specialty. Statistical analysis showed that there was an association between length of stay and surgical specialty (Tables 1 and 2).…”
mentioning
confidence: 98%
“…Studies [19,20] have stated that emergency teams are constantly in contact with the unpredictability, This article is available at: www.intarchmed.com and www.medbrary.com the severity of patients´ situations and the limitation of human, material and structural resources, greatly influencing the quality of care provided.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, teamwork that is cohesive and integrates the members from conception to execution is an efficient means to obtain high quality, safe care for patients (10)(11)(12) . However, teamwork within the context of the particularities of emergency hospital services is a challenge for nurses (11,(13)(14) . Even with the advancement of healthcare policies that establish the organization of an emergency care system in Brazil, hospital services continue to be the first point of entry of people in emergency situations (13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%